2019
DOI: 10.1016/j.memsci.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose hollow fibers for organic resistant nanofiltration

Abstract: Cellulose is the most abundant biopolymer, but it is difficult to process due to its low solubility in most of the solvents. In this work, we demonstrate the preparation, of self-standing and defect-free cellulose hollow fiber membranes made by a sustainable process for filtration in organic solvent medium. The hollow fibers were made by the simple spinning technique using ionic liquids as a solvent. The spun solutions were prepared with three different ionic liquids, having imidazoliumbased cations and acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…Although cellulose membranes and its derived CMS membranes have been reported in the literature 19 , 20 , 26 , asymmetric cellulose-based carbon hollow fiber membranes have never been reported for gas separation. Cellulose has strong inter- and intra-chain hydrogen bonds, which prevents solubility in most common solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cellulose membranes and its derived CMS membranes have been reported in the literature 19 , 20 , 26 , asymmetric cellulose-based carbon hollow fiber membranes have never been reported for gas separation. Cellulose has strong inter- and intra-chain hydrogen bonds, which prevents solubility in most common solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is difficult to control the membrane formation phase inversion process for such a system, which ultimately determines the structure and morphology of regenerated hollow fiber cellulose precursors. Furthermore, it has been found that water-filled cellulose membranes experience morphology collapse when dried directly from water 26 . Accordingly, a proper drying process to maintain the formed pore structure is required.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Li et al reported the fabrication of permeable and antifouling UF membranes using bacterial cellulose with mussel-inspired dopamine and graphene oxide [ 106 ]. Graphene-oxide nanosheet functionalized phosphorylated chitosan (PCS) NF membranes also exhibited high flux, separation efficiency and antifouling performance [ 107 ]. Therefore, due to their unique characteristics such as high mechanical strength, tunable weight, surface properties, strong networking abilities and antifouling, biopolymers and their derivatives have been used to devise pressure-driven membranes.…”
Section: Biopolymer-based Dye Removal Technologiesmentioning
confidence: 99%
“…This proves the feasibility of using ionic liquids for cellulose dissolution, as well as the practicability of cellulosic membrane in various applications involving a solvent medium. On the other hand, ionic liquids such as 1-ethyl-3-methyimidazolium diethyl phosphate, 1,3-dimethylimidazolium dimethyl phosphate, and 1-butyl-3-methylimidazolium chloride were also employed by other groups of researcher as the solvent to prepare cellulosic membrane for dye, protein, and oil retentions [ 107 , 108 , 109 ]. The membrane performances showed that all ionic liquids can be good solvents for cellulose.…”
Section: Substrate Preparation Via Phase Inversionmentioning
confidence: 99%